Management skills and strategic planning in a peruvian university - Paredes-Pérez, Marco A.J. (2021)
Objective. Determine the relationship between managerial skills and strategic planning at the Universidad Peruana los Andes, Ayacucho branch, 2016. Methods. The approach was quantitative, basic type, correlational level and descriptive-correlational design. Observation was applied, as well as inductive-deductive and analytic-synthetic methods. The instruments were the 16-item management skills questionnaire and the 20-item strategic planning questionnaire. The census sample consisted of 101 employees, including managers, teachers and administrative staff. Results. There is a significant relationship between managerial skills and strategic planning with a p-value of 0 and a Kendall Tau-b value of 0.294. Conclusions. The better perception of management skills management, the better strategic planning results.